Woman and urban transport - Montoya-Robledo, V (Edward Elgar Publishing, 2024)
This chapter engages with the intersection of gender and urban transport in cities, highlighting how men and women use transportation. It explores the interplay of gender with factors such as class, race, ethnicity, sexuality, and ability in urban transport dynamics. The gendered aspects include usage patterns, trip characteristics, vehicle preference, risks faced, and coping mechanisms during transit. Emphasizing the diversity among women, the chapter examines how poverty and inequality exacerbate transportation poverty for specific groups. It concludes with a study of the gender-based violence that women who are domestic workers suffer while commuting in Latin American cities. Factors such as long and overcrowded commutes, informal working conditions, and the naturalization of subordination contribute to the violence experienced in Latin American transit, and the role of law in responding to them.